2020
DOI: 10.1080/21655979.2020.1771068
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cells in tumor microenvironment promoted the neuropathic pain via paracrine inflammatory and growth factors

Abstract: Neuropathic pain associated with cancers was caused by tumor itself or tumor therapy, which was aggravated by sensitizing nociceptor sensory neurons. The tumor microenvironment contributed to tumorigenesis, tumor progress, tumor metastasis, tumor immune resistance, tumor chemotherapy, and tumor immunotherapy. In the current study, we explored the contributions of the infiltrated dendritic cells insulted by Wnt1 in tumor microenvironment to neuropathic pain associated with cancers. The different transcriptome o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 51 publications
0
33
0
Order By: Relevance
“…Tumor-related studies have shown that the upregulation of factor E2F1 can cause pathological pain. The paracrine factors interacting with their receptors could cause the activation of downstream transcription factors such as E2F1 to upregulated expression of genes associated with pain [29]. Studies have shown that factor MITF can promote and survive osteoclast precursors, greatly enhancing the incidence of bone metastasis pain [30].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-related studies have shown that the upregulation of factor E2F1 can cause pathological pain. The paracrine factors interacting with their receptors could cause the activation of downstream transcription factors such as E2F1 to upregulated expression of genes associated with pain [29]. Studies have shown that factor MITF can promote and survive osteoclast precursors, greatly enhancing the incidence of bone metastasis pain [30].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells, which usually colonize normal tissues, can form a tumor microenvironment (TME) together with stromal cells, immune cells and their secretory factors and extracellular matrix (ECM) components. Studies have shown that immune cells and the cytokines produced by them, including immunosuppressive and inflammatory cytokines, play a dual role in promoting or preventing cancer development ( Junttila and de Sauvage, 2013 ; Lianyuan et al, 2018 ; Wang et al, 2020 ). Nevertheless, few studies have been conducted on the role of MRGBP in the immune microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is important to better understand the molecular mechanisms underlying NP. To simulate NP in vivo, animal experiments commonly use the method of direct nerve damage, especially to the sciatic nerve [2,[25][26][27]. Considering the involvement of lncRNAs in the pathophysiological process of NP, a rat model of NP induced by CCI was adopted in the current study to comprehensively clarify the characteristics and regulatory mechanisms of lncRNAs in NP development.…”
Section: Discussionmentioning
confidence: 99%
“…Neuropathic pain (NP) is recognized as a kind of chronic pain which is persistent regular pain and leads to 11-19% of incidence in adult population [1,2]. NP is a significantly complex pain disorder arising from abnormalities in the somatosensory nervous system, reducing the life quality of patients and triggering their financial and mental burden [3][4][5].…”
Section: Introductionmentioning
confidence: 99%